Exclusion of Unionized Workers from Employment Standards Law - Fairey, David (Relations industrielles / Industrial Relations, 2009)
The technique of permitting unions to derogations from core employment standards has been increasingly advocated as a means of making labour law more flexible while still protecting workers since the union is considered to bring countervailing power in support of workers’ preferences. The new British Columbia Employment Standards Act contains a broad union derogation provision. Industrial relations experts have commented that employment standards that permit the opting out of statutory employee protections in this way invites corrupt arrangements between employers and employer-dominated unions. Using the new BC statute as a case study, the assumption that requiring the union’s consent to derogation from core standards ensures that the derogation reflects workers’ preferences is tested using two sources of empirical data: collective agreements entered into by an employer friendly union (the Christian Labour Association of Canada); and collective agreements in which the union had neither the opportunity nor the strength to prevent derogation.